Zein/MCM-41 Nanocomposite Film Incorporated with Cinnamon Essential Oil Loaded by Modified Supercritical CO2 Impregnation for Long-Term Antibacterial Packaging - Xiaojing Liu; Jingfu Jia; Shulei Duan; Xue Zhou; Anya Xiang; Ziling Lian; Fahuan Ge (MDPI AG, 2020)
Antimicrobial medicine and food packages based on bio-based film containing essential oils have attracted great attention worldwide. However, the controlled release of essential oils from these film nanocomposites is still a big challenge. In this study, a long-term antibacterial film nanocomposite composed of zein film and cinnamon essential oil (CEO) loaded MCM-41 silica nanoparticles was prepared. The CEO was loaded into MCM-41 particles via modified supercritical impregnation efficiently with a high drug load (>40 wt%). The morphologies of the prepared nanoparticles and film nanocomposite were characterized by a scanning electron microscope. The release behaviors of CEO under different temperatures, high humidity, continuous illumination and in phosphate buffer solution (PBS) solution were investigated. The results showed that the film nanocomposite had an outstanding release-control effect. The addition of MCM-41 nanoparticles also improved the mechanical properties of zein films. The antibacterial effect of CEO was significantly prolonged by the film nanocomposite; indicating the CEO film nanocomposite fabricated via modified supercritical CO2 impregnation was a potential long-term antibacterial medicine or food package material.